PENINGKATAN HASIL BELAJAR IPA DENGAN MODEL PEMBELAJARAN MIND MAP UNTUK PESERTA DIDIK KELAS III DI SD N CIPOCOK JAYA 2 - Ade Ade; Zerri Rahman Hakim; Lili Fajrudin; Euis Fidyana (Journal of Professional Elementary Education, 2023)
The teacher is responsible for preparing everything in learning activities so that they can run effectively and efficiently to be able to support student learning outcomes to the maximum. Applying a learning model that can attract students' interest and invites students to play an active role in building the knowledge they have through the mind map learning model, especially in science learning. This research is a Classroom Action Research (CAR) aimed at improving the learning process to get maximum learning outcomes. The research was conducted in class III of SD N Cipocok Jaya 2 in science learning. The results showed that the completeness of the pre-cycle learning outcomes was 43.33% of all students. In cycle I, learning outcomes increased by 16.7%, and the percentage level in cycle I reached 60%. The frequency of students who were declared to have passed the KKM in science learning increased from initially only 13 students to 18 students. Deficiencies made in learning cycle I have been corrected in the implementation of learning Cycle II and showed learning outcomes increased by 26.67% and the percentage level in Cycle II reached 86.67%. The frequency of students who were declared to have passed the KKM in science learning in cycle I increased from initially only 18 students to 26 students in cycle II